The Terezita Romo Papers: Capturing the Spirit of Collective Action in Archives - Ulinskas, Moriah (KULA)

(untitled) (University of Victoria Libraries, 2018)
This article addresses the Terezita Romo Papers, one of a handful of archival collections of the Royal Chicano Air Force—a large collective of young, mostly immigrant or first-generation Mexican American artists and activists who produced countless community events and art projects and programs in Sacramento, California during the second half of the twentieth century. While membership of the Royal Chicano Air Force (RCAF) and its activities are hard to calculate, its history has been shaped by a tendency towards iconization of the group’s male founders in archival description. Specifically, where collections are described to highlight the unique contributions of individuals, it is difficult to retain and promote the collective voice of action which made so many of these movements successful. Using the papers of Tere Romo, one member of the RCAF, this paper looks at how the archives of the RCAF have tended towards iconization—overshadowing the contributions of its female members—and explores ways in which archivists can reconsider the language of archives when processing and describing materials documenting collective action in American history.